Feasibility analysis of implementing an On Bill Financing program to promote energy-efficiency in Dubai-UAE - Zulfiquar Kamal, Hasan (2022)
In this paper, we examine the factors that may influence the implementation of an OnBill Financing (OBF) program for promoting energy efficiency in Dubai. The data was collected using a semi-structured expert on expert interview method. Interviews were conducted with institutional stakeholders involved in OBF program implementation. A forcefield diagram was created from the interview responses to understand better the iden tified conducive and deterrent forces that must be considered when implementing an OBF program locally. The main finding of the qualitative review suggests that an OBF program could be implemented locally in Dubai. The findings also show that implementation is not without challenges. A tailored OBF program that addresses the repayment model and covered equipment/projects under the program can mitigate these hurdles.